THE STUDENTS’ PERCEPTIONS OF USING GRAMMARLY AS A LEARNING TOOL IN WRITING SKILLS - Annisa Sakilah; Husnil Khotimah; Anisa Tri Angelia; Habib Azizi (Journal of Advances in Linguistics and English Teaching (JALET), 2025)
Writing is one of the most challenging skills for English as a Foreign Language (EFL) learners, especially for first-semester students who are still adapting to academic writing. Technological tools such as Grammarly have been widely used to support students in improving writing accuracy and providing immediate feedback. This study aims to explore first-semester students’ perceptions of using Grammarly in English writing at STAIN Madina. A qualitative descriptive research design was employed, involving ten students from the English Education Department selected through purposive sampling. Data was collected through semi-structured interviews, classroom observations, and documentation of students’ writing drafts and Grammarly feedback. The data were analyzed using the interactive model proposed by Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings reveal that students generally have positive perceptions of Grammarly as a writing support tool. Grammarly helps students identify grammatical errors, increases their confidence in writing, and promotes learner autonomy. However, the study also found challenges such as overdependence on the tool and occasional inaccuracies in feedback. The study concludes that Grammarly is effective as a supportive tool in EFL writing instruction when used critically and combined with lecturer guidance.